INTERAKSI SOSIAL DAN NILAI-NILAI KERUKUNAN DI SIPIROK, TAPANULI SELATAN - Dinda Oktovia; Sakti Ritonga (NUANSA: Jurnal Penelitian Ilmu Sosial dan Keagamaan Islam, 2025)
This research aims to examine how social interaction and values of harmony between Muslims and Christians take place in Huta Suhut Village, Sipirok Sub-district, South Tapanuli. The study employed a qualitative descriptive approach by collecting data through in-depth interviews with traditional leaders, religious leaders, the village head, youths, and the general community. The findings show that the Sipirok community is diverse in terms of religion, social life, economy, and culture. However, harmony is maintained through strong kinship ties, clan relations, and shared traditions. Traditional leaders and community figures also play an important role in maintaining intergroup relations so that differences do not lead to conflict. The practice of religious harmony and tolerance can be observed in three main aspects: social life, cultural life, and religious practices. Thus, it can be concluded that conflict does not surface because of the strong kinship ties and the role of community leaders in uniting various social groups.